2001
DOI: 10.1023/a:1010469900892
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Contextual Predictors of Involvement in Twelve‐Step Self‐Help Groups After Substance Abuse Treatment

Abstract: Drawing on ecological and narrative theories of self-help groups, this study tests a multilevel model predicting self-help group involvement among male veterans who received inpatient substance abuse treatment. Following K. Maton (1993), the study moves beyond the individual-level of analysis to encompass variables in the treatment and post-treatment social ecology. Surveys administered to patients (N = 3,018) and treatment staff (N = 329) assessed these predictor domains and self-help group involvement 1 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 46 publications
3
58
0
1
Order By: Relevance
“…Sharing of lived experience and within-group practice in caregiving can also encourage acceptance of their past, discourage denial of their present situation, and encourage coping with the existing family problems. The effort of behavioural change is usually reinforcing as the group help group members admit their problems in caregiving and approve the extinction of undesirable habits (Mankowski, Humphreys and Moos, 2001). …”
Section: The Conceptual Basis Of Mutual Support Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sharing of lived experience and within-group practice in caregiving can also encourage acceptance of their past, discourage denial of their present situation, and encourage coping with the existing family problems. The effort of behavioural change is usually reinforcing as the group help group members admit their problems in caregiving and approve the extinction of undesirable habits (Mankowski, Humphreys and Moos, 2001). …”
Section: The Conceptual Basis Of Mutual Support Groupsmentioning
confidence: 99%
“…What emerges from the studies reviewed in this paper is that they can be effective in building participants' personal skills, empowerment, and social support. Different self-help programmes and initiatives which are widely used across Canada, the U.S. and the U.K. for a wide range of sectors of the population, such as those with grief and bereavement, chronic physical diseases, and substance abuse (Carpenter, 1997;Lorig et al, 2000;Mankowski et al, 2001), have attracted a great deal of research attention. However, from the results of this literature review, few research studies hitherto have investigated the helping process and effects of mutual support groups for family members in caring for a relative with 21 severe mental illness.…”
Section: Qualitative Exploratory Studiesmentioning
confidence: 99%
“…Overall, seeking to identify individual predictors of 12-step attendance has been challenging. A unique study tested a multilevel model of predictors of post-treatment 12-step attendance that included individual-level (client demographics and cognitive characteristics) as well as treatment and post treatment socio-ecological domains -e.g., type of housing, availability of 12-step meetings in the area (Mankowski et al, 2001). Significant individual-level predictors were education level, prior 12-step exposure, abstinence goal, endorsement of the disease model, religious beliefs and behaviors; socio-ecological predictors were treatment 12-step orientation, and living in group housing.…”
Section: Individual-level Predictorsmentioning
confidence: 98%
“…Humphreys, Huebsch, Finney, , 1999;McKay, McLellan, Alterman, Cacciola, Rutherford and O'Brien, 1998;Morgenstern et al, 1997; Tonigan et al, 2006). Results for other demographic characteristics including race and gender have been inconsistent across studies (Emrick, Tonigan Montgomery and Little, 1993;Humphreys, 1991;Kessler, Mickelson and Zhao, 1997;Mankowski, Humphreys and Moos, 2001). A comprehensive study examining a large number of potential individual-level predictors (demographics, personality characteristics, clinical, and cognitive processes) reported that only baseline abstinence and longer substance use significantly predicted subsequent 12-step attendance levels (McKay et al, 1998).…”
Section: Individual-level Predictorsmentioning
confidence: 99%
See 1 more Smart Citation